2013
DOI: 10.5897/sre2013.5702
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant biostimulants on fruit cracking and quality attributes of pomegranate cv. Kandhari kabuli

Abstract: Himachal Pradesh during the year 2008 to 2009. The experiment consisted of 19 treatments with three replications. The pomegranate trees cv. kandhari kabuli under investigation were subjected to foliar spray of biostimulants viz. vipul, spic cytozyme, homobrassinolides, biozyme crop plus, vipul + homobrassinolides and control. The study was conducted to determine the effect of plant biostimulants on cracking and quality of fruits. Cracking is a disorder where fruit surface cracks mainly due to heavy irrigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The use of biostimulants based on titanium compounds did not alter the fruit firmness, which was comparable to the firmness in the control test [47]. The use of spic cytozyme containing essential plant nutrients and growth biostimulants in the amount of 4 mL/L significantly reduced the cracking of pomegranate fruit [58]. In addition to improving mechanical properties, biostimulants change the shape and colour of fruits and vegetables.…”
Section: Impact Of Biostimulants On Physical Characteristicsmentioning
confidence: 91%
“…The use of biostimulants based on titanium compounds did not alter the fruit firmness, which was comparable to the firmness in the control test [47]. The use of spic cytozyme containing essential plant nutrients and growth biostimulants in the amount of 4 mL/L significantly reduced the cracking of pomegranate fruit [58]. In addition to improving mechanical properties, biostimulants change the shape and colour of fruits and vegetables.…”
Section: Impact Of Biostimulants On Physical Characteristicsmentioning
confidence: 91%
“…Abubakar et al (2012) [1] studied the effect of foliar application of plant biostimulants in pomegranate and reported that, plant biostimulants significantly improved flowering, yield, return bloom and reduced the fruit drop. Aziz et al, (2013) [3] revealed that, the application of plant biostimulants significantly improved flowering, yield also reduced the fruit drop in pomegranate.…”
Section: Growth Parametersmentioning
confidence: 99%
“…Anthocyanin (28) show that the increase in fruit color is due to increased fruit content of anthocyanin, which is due to the high accumulation of carbohydrates. In the grape variety Flam Seedles color and phenolic compounds increased by increasing the level of fertilizer (29).…”
Section: Crop Of Fruitsmentioning
confidence: 99%